Prevention of RhD Alloimmunization: A Comparison of Four National Guidelines - Sperling, Jeffrey D.; Dahlke, Joshua D.; Sutton, Desmond; Gonzalez, Juan M.; Chauhan, Suneet P. (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare national guidelines on the prevention of RhD alloimmunization.Study Design We performed a review of four national guidelines on prevention of alloimmunization from the American Congress of Obstetricians and Gynecologists, Royal College of Obstetricians and Gynaecologists, Society of Obstetricians and Gynaecologists of Canada, and The Royal Australian and New Zealand College of Obstetricians and Gynaecologists. We compared the indications/contraindications, timing, dosing, formulation and route of anti-D immune globulin, and management of unique circumstances. The references were compared with regard to the number of randomized control trials, Cochrane Reviews, and systematic reviews/meta-analyses cited.Results Variation exists in recommendations on the timing and need for consent prior to routine antenatal anti-D immune globulin administration, prophylaxis for unique circumstances (e.g., threatened abortion < 12 weeks, complete molar pregnancy), and the use of cell-free fetal DNA testing for fetal RhD genotype.Conclusion These variations in recommendations reflect the heterogeneity of the literature on the prevention of alloimmunization and highlight the need for synthesis of evidence to create an international guideline on prevention of alloimmunization. This may improve safety, quality, optimize outcomes, and stimulate future trials.
Keywords: clinical; guideline; alloimmunization; hydrops fetalis; disease; anti-D immunoglobulin; fetomaternal hemorrhage